Estudo da motilidade gástrica em ratas prenhes diabéticas e não diabéticas - Matos, Juliana Fernandes de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Several hormonal and physiological changes that occur during pregnancy directly affect gastrointestinal motility (GI), however, very little is known about the relationship between the electrical and mechanical activities of the stomach and its implications. The aim of this study was to compare the female sex hormones, with profiles of gastrointestinal motility using AC biosusceptometry (BAC) in pregnant rats. Seven female Wistar rats (weighing 250-350 g) were used and all procedures were approved by the local Ethics Committee of animal. Laparotomy was performed on anesthetized rats and a magnetic marker (3.5 mm in diameter and 3.0 mm height) was implanted in the distal stomach. After 10 days of recuperation, the mice were put to mate until confirmation of pregnancy. Fed animals were anesthetized (mg pentobarbital 30 / kg) and kept supine for recording the signal with a sensor 30 min BAC placed on the abdominal surface on days 0, 7, 14 and 20 of gestation. Statistical analysis was performed by Student's t test statistical Newman-Keuls and a P value of .05 was considered statistically significant. The frequency of contraction of the stomach was 74 mHz ± 3, 67 ± 7 mHz, 59 mHz ± 6 (p <0.05 vs day -1) and 71 ± 5 mHz on days -0, -7, -14, and -20, respectively. The values of 44 ± 15 pg / mL and 31 ± 9 pg / ml 25 ± 6 pg / ml, 22 ± 9 pg / ml on days -0, -7, -14 and -20, respectively, obtained by 17ß- estradiol were not statistically significant. The values of progesterone were 13 ± 6 pg / ml at 54 ± 15 pg / ml, 127 ± 42 pg / ml (p <0.05 vs day-1), 22 ± 13 pg / mL on day -0, - 7, -14 and -20, respectively. A linear correlation (Pearson's test) between the lower frequency gastric and increased levels of progesterone was 80% (p <0.0000001). Until then, the relationship between changes in motility and hormone were not described in detail, but with the work that we were able to demonstrate the high correlation between progesterone concentration ...

Várias mudanças hormonais e fisiológicas que ocorrem durante a gravidez afetam diretamente a motilidade gastrointestinal (GI), no entanto, muito pouco se sabe sobre a relação entre as atividades elétricas e mecânicas do estômago e suas implicações. O objetivo desse trabalho foi comparar os hormônios sexuais femininos, com perfil de motilidade gastrointestinal, usando AC biossusceptometria (BAC), em ratas prenhes. Sete ratas fêmeas Wistar (pesando 250-350 g) foram utilizadas e todos os procedimentos foram aprovados pelo Comitê de Ética local de animal. A laparotomia foi realizada em ratas anestesiadas e um marcador magnético (3,5 mm de diâmetro e 3,0 mm de altura) foi implantado no estômago distal. Depois de 10 dias de recuperação, os ratos foram colocados para acasalar até a confirmação da gravidez. Animais alimentados foram anestesiados (mg, pentobarbital 30 / kg) e mantidos em decúbito dorsal para a gravação do sinal de 30 min com um sensor de BAC colocada sobre a superfície abdominal nos dias 0, 7, 14 e 20 de gestação. A análise estatística foi realizada pelo teste estatístico t de Student-Newman Keuls e um valor de P de 0,05 foi considerado estatisticamente significativo. A frequência de contração do estômago foi de 74 ± 3 mHz, 67 ± 7 mHz, 59 ± 6 mHz (p <0,05 vs dia-1), e 71 ± 5 mHz nos dias -0, -7, -14 e -20, respectivamente. Os valores de 44 ± 15 pg / mL, 31 ± 9 pg / mL, 25 ± 6 pg / mL, 22 ± 9 pg / mL nos dias -0, -7, -14 e -20, respectivamente, obtidas por 17ß-estradiol não foram estatisticamente significativas. Os valores de progesterona foram de 13 ± 6 pg / mL, 54 ± 15 pg / ml, 127 ± 42 pg / ml (p <0,05 vs dia-1), 22 ± 13 pg / mL no dia -0, -7, -14 e -20, respectivamente. A correlação linear (teste de Pearson) entre a diminuição da frequência gástrica e aumento dos níveis de progesterona foi de 80% (p <0,0000001). Até então, as relações entre as ...
Keywords: Sistema gastrointestinal - Motilidade - Tomografia; Hormonios sexuais; Rato como animal de laboratorio; Comprimidos (Medicina) - Desintegração; Biomagnetismo; Biosusceptometria de Corrente Alternada; Alternated Current Biosusceptometry